Linear Decrease in Athletic Performance During the Human Life Span - Ganse, Bergita; Ganse, Urs; Dahl, Julian; Degens, Hans (Frontiers in Physiology, 2018)
Master athletes maintain high physical activity levels and have better health than age-matched non-athletes. World records show accelerated declines after age 70 in swimming, long-distance running and sprint performance. However, less is known about age-related performance declines in the general master athlete population and whether decline rates differ between disciplines and genders. We interrogated a dataset including all track and field athletes of North Rhine from 2001 to 2014 to assess age-related changes in performance. 27,088 results of athletes between 11 and 89 years of age in 12 disciplines were analysed by regression statistics. The analyses showed an accelerated decline beyond the age of 70 in sprint, middle- and long-distance running, while in throwing and jumping disciplines the performance continued a linear decline. Patterns of decline differed between men and women. The steepest declines were observed in javelin throw and 400m (women), and in pole vault and 800m (men). In conclusion, performance declines in ageing depend more on the specific profile of requirements than previously assumed.